1976
DOI: 10.1093/oxfordjournals.aje.a112273
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Trial of Influenza Vaccines

Abstract: Commercially prepared zonally and chromatographically purified bivalent (A/England-B/Mass) and monovalent (B/Hong Kong) inactivated influenza vaccines were given to 438 individuals 6-33 years old. The vaccines had been examined for antigen content by chick cell agglutination (CCA) tests and electron microscopic particle count determinations. Endotoxin and pyrogen content were determined by limulus amebocyte lysate (LAL) and rabbit pyrogenicity assays; and egg-associated protein contamination was estimated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Several factors may account for the low or negligible induction of anti-NA antibodies by SV. First, ether- and detergent-disrupted SVs are poor immunogens in mice and humans [ 31 , 32 ] because the viral RNA in the SVs, which affects APC activation, is degraded [ 13 ]. Second, the HA protein, which binds to sialic acid receptors, is preferentially endocytosed by APCs over NA or other viral proteins, subsequently inducing antibodies mainly against HA.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may account for the low or negligible induction of anti-NA antibodies by SV. First, ether- and detergent-disrupted SVs are poor immunogens in mice and humans [ 31 , 32 ] because the viral RNA in the SVs, which affects APC activation, is degraded [ 13 ]. Second, the HA protein, which binds to sialic acid receptors, is preferentially endocytosed by APCs over NA or other viral proteins, subsequently inducing antibodies mainly against HA.…”
Section: Discussionmentioning
confidence: 99%
“…Local reactions were reported in from 20-57% of the recipients aged 6-33 y. 87 Clinical trials reported swelling up to 7.3% of vaccinated elderly aged 60 y and older. Local reactions are reported more frequently among the high-dose recipients (36% reported pain) than among standard-dose flu vaccine recipients (24% reported pain) in 65 y of age or older in US.…”
Section: Cochrane Review and Its Limitationsmentioning
confidence: 99%
“…Generally, systemic symptoms, for example, fever, malaise, or myalgia, occur more often in individuals not vaccinated with TIV in the past and in younger subjects. 53 In this study, athletes of the N group were 3 years younger, whereas 21% of the N + S group was more often vaccinated against influenza in the past (both differences not statistically significant). The crucial conclusion is that a second flu vaccination during the same influenza season does not increase the frequency of adverse events, both local and general.…”
Section: Discussionmentioning
confidence: 51%